A Longitudinal Study on Online Sexual Engagement, Victimization, and Psychosocial Well-Being - Reer, Felix; Wendt, Ruth; Quandt, Thorsten (Frontiers in Psychology, 2021)
Several cross-sectional studies have shown that practices like ‘sexting’, or sexualized forms of self-presentation on social media (‘sexy self-presentation’) were associated with an increased risk of experiencing negative consequences, such as sexual victimization or cyberbullying. Online sexual engagement was also found to be associated with lower levels of psychosocial well-being, in particular less mental health. However, the direction of these relationships often remained unclear since longitudinal studies are scarce. Further, most existing studies were based on non-representative adolescent samples. The current study examined the prevalence of sexting, sexy self-presentation and online sexual victimization among a representative sample of German Internet users aged 14 to 64 years. Longitudinal relationships between online sexual engagement, victimization experiences and psychosocial well-being were investigated over a period of 1 year. Our results indicate that online sexual engagement and victimization experiences are relatively widespread, and, to a certain degree, also occur among older individuals. Confirming previous findings, our cross-sectional results show that online sexual engagement, victimization experiences and mental problems are intercorrelated. Concerning long-term associations, we detected a significant relationship between sexting willingness at T1 and more victimization experienced one year later, while no significant longitudinal associations with lower levels of psychosocial well-being were identified.